Providensia Allah dan Tanggung Jawab Manusia dalam Kitab Yosua 21:45: Analisis Teologis dan Naratif - Refamati Gulo (Views : Jurnal Teologi dan Biblika, 2025)
God is a living, independent person who is fully sovereign over all of His creation. Meanwhile, human beings and the rest of creation are completely dependent on Him. Without God's providence and control, all things would perish. Within the framework of His providence, God actively carries out His will to fulfill the divine purpose. This study is motivated by the importance of understanding how divine action and human responsibility work synergistically, especially in the narrative of the Book of Joshua. This study aims to examine the relationship between God's providence and human responsibility theologically and narratively, and examine its implications for the understanding of contemporary Christian faith. It uses a qualitative approach with theological and narrative analysis methods, which allow for an in-depth exploration of the text of the Book of Joshua in its historical and theological context. The results show that God's providence does not negate the role of humans, but rather invites people to be actively involved in His plan. God's promises in the Book of Joshua were fulfilled through the concrete actions of the obedient and believing people of Israel. Thus, the synergy between God's sovereignty and human responsibility is key in understanding how God's plan of salvation is carried out. This narrative affirms that true faith is always manifested in action, and that human participation is not only essential, but also desired by God in His covenant relationship.